2010
DOI: 10.1177/1059840510365154
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Blood Pressure, Body Mass Index, and Acanthosis Nigricans in School-Age Children

Abstract: The purpose of this retrospective quantitative study was to examine the relationships among acanthosis nigricans (AN), body mass index (BMI), blood pressure (BP), school grade, and gender in children attending elementary school located in South West Texas. Data were collected by attending school district nurses. Researchers reviewed 7,026 previously collected records from a state mandated public school health screening program in elementary school Grades 3, 5, 7, and 9, conducted by school nurses. Of 7,026 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
4
11
0
Order By: Relevance
“…Study results in Table 4 show the comparison of gender, BP, and BMI’s effects on AN between SY 06-06 and SY 08-09. These results were the same as our previous study in 2010 (Otto et al, 2010). That is, a female child was more likely (OR = 1.46) to have a positive AN marker than a male child.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Study results in Table 4 show the comparison of gender, BP, and BMI’s effects on AN between SY 06-06 and SY 08-09. These results were the same as our previous study in 2010 (Otto et al, 2010). That is, a female child was more likely (OR = 1.46) to have a positive AN marker than a male child.…”
Section: Resultssupporting
confidence: 92%
“…These results were the same as our previous study in 2010 (Otto et al, 2010). That is, a female child was more likely (OR ¼ 1.46) to have a positive AN marker than a male child.…”
Section: Study Results Insupporting
confidence: 90%
“…Psychiatric patients receiving antipsychotic medications were targeted in three studies [ 40 , 41 , 45 ], since these medications are associated with significant weight gain [ 46 ]. One study included children and adolescents at high-risk of MetS, with a first-degree family history of type 2 DM, obesity or acanthosis nigricans [ 42 ], due to the potential link to underlying insulin resistance [ 47 , 48 ]. Healthy volunteers were the subjects of one study [ 36 ] (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although younger, southwest Texas school children in grades 3, 5, 7, and 9 were reported to be obese (22%), positive for AN (23%), and have elevated BP (>90th percentile, 21%). 14 Similarly, Urrutia-Rojas et al 15 reported that among among 1066 Hispanic students 10 to 12 years old, the prevalence of obesity was 31.9%, the prevalence of AN was 17%, and elevated BP at the 95% cutoff was 23.6%. The reported prevalence in these studies is somewhat lower than that in our study, presumably because of the younger age and/or different cutoff criteria used for BP.…”
Section: Discussionmentioning
confidence: 97%